2006
DOI: 10.1007/s10705-005-6082-6
|View full text |Cite
|
Sign up to set email alerts
|

Partial balance of nitrogen in a maize cropping system in humic nitisol of Central Kenya

Abstract: The application of nitrogen in a soil under agricultural production is subject to several pathways including de-nitrification, leaching and recovery by an annual crop. This is as well greatly influenced by the management practices, nitrogen source and soil conditions. The main objective of this study was to investigate the loss of nitrogen (N) through nitrous oxide (N 2 O) emissions and mineral N leaching and uptake by annual crop as influenced by the N source. The study was carried out at Kabete in Central Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Apparently, this was one of the very limited studies in Africa that looked into both wet and dry seasons and estimated annual N 2 O emissions of 1.54 kg N hm -2 from mineral fertilizer application and 0.97 kg N hm-2 from animal manure. However, similar urea broadcasting at 60 kg hm -2 by Kimetu et al (2006) only yielded up to T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 T6 Season I Season II Season III plant captured C (kg C hm -2 ) (e ) T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 (a, b), N-uptake (c, d) and C captured (e, f) by maize grown on experimental plots under six treatments at the UZ-Farm and DT-Centre 2.9 μg N 2 O-N and an annual total of 0.1 kg N 2 O-N hm -2 that is less than some of the N 2 O inventories from our study. There could therefore be a problem of heterogeneity in N inputs for area based measurements and in some parts of Europe some grazed pastures can have cattle urine patches that add 1000 kg N hm -2 , and yet many N 2 O measurements studies are carried out using randomly located chambers (Rees RM 2010, personal communication).…”
Section: Discussionmentioning
confidence: 80%
“…Apparently, this was one of the very limited studies in Africa that looked into both wet and dry seasons and estimated annual N 2 O emissions of 1.54 kg N hm -2 from mineral fertilizer application and 0.97 kg N hm-2 from animal manure. However, similar urea broadcasting at 60 kg hm -2 by Kimetu et al (2006) only yielded up to T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 T6 Season I Season II Season III plant captured C (kg C hm -2 ) (e ) T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 T6 T1 T2 T3 T4 T5 (a, b), N-uptake (c, d) and C captured (e, f) by maize grown on experimental plots under six treatments at the UZ-Farm and DT-Centre 2.9 μg N 2 O-N and an annual total of 0.1 kg N 2 O-N hm -2 that is less than some of the N 2 O inventories from our study. There could therefore be a problem of heterogeneity in N inputs for area based measurements and in some parts of Europe some grazed pastures can have cattle urine patches that add 1000 kg N hm -2 , and yet many N 2 O measurements studies are carried out using randomly located chambers (Rees RM 2010, personal communication).…”
Section: Discussionmentioning
confidence: 80%
“…The Intergovernmental Panel on Climate Change (IPCC) guidelines for the calculation of national greenhouse gas inventories includes three tiers of approaches; the simplest, which is used widely for national inventories in SSA, assumes that 1% of applied fertilizer is lost as N 2 O in direct emissions annually [Intergovernmental Panel on Climate Change, 2006]. Among field studies that have been conducted in SSA, emission factors for a given cropping season or year are well below 1%, with an overwhelming majority under 0.75% [Chikowo et al, 2004;Baggs et al, 2006;Kimetu et al, 2006;Brümmer et al, 2008;Dick et al, 2008;Chapuis-Lardy et al, 2009;Mapanda et al, 2010Mapanda et al, , 2011Mapanda et al, , 2012b, except when fertilization rates exceeded 200 kg N ha À1 Baggs et al, 2006;Predotova et al, 2010;Lompo et al, 2012], though see two exceptions Dick et al, 2008] (Figure 4). The low-emission factors are also found in laboratory incubations Baggs, 2004, 2005;Gentile et al, 2008], although it should be emphasized that few field studies and no laboratory studies included measurements across an entire year.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, incorporation of maize straw and leaf residue into soil increased annual CO 2 fluxes substantially (emissions rose from 2.5 to 4.0 and 2.4 to 3.4 Mg C ha −1 yr −1 for clay and sand soils, respectively; Sugihara et al, 2012), although a study in Madagascar showed that incorporation of rice-straw residue resulted in larger fluxes of CO 2 but reduced N 2 O emissions due to N immobilization (Rabenarivo et al, 2014). In contrast, incorporation of Tithonia diversifolia (tithonia) leaves led to greater N 2 O emissions compared to urea application in maize fields in Kenya (Sommer et al, 2015;Kimetu et al, 2007). The higher N 2 O emissions after incorporation of Tithonia diversifolia were attributed to high levels of nitrate and available carbon in the soil caused by the application that subsequently enhanced denitrification rates.…”
Section: Croplandsmentioning
confidence: 99%